Asthma, allergic rhinitis and eczema among parents of preschool children in relation to climate, and dampness and mold in dwellings in China. (September 2019) - Wang, Juan; Zhao, Zhuohui; Zhang, Yinping; Li, Baizhan; Huang, Chen; Zhang, Xin; Deng, Qihong; Lu, Chan; Qian, Hua; Yang, Xu; Sun, Yuexia; Sundell, Jan; et al.
Abstract: The main aim was to study associations between asthma, allergic rhinitis and eczema among adults across China and dampness and mold at home. Young adults ( N  = 40, 279) in eight cities in China answered a questionnaire in 2010–2012 (response rate 75.0%). Data on asthma, allergic rhinitis, eczema and the home environment was assessed by the questionnaire. Climate data was obtained from China Meteorological Administration and the website of Weather Underground. Health associations were analyzed by two-level logistic regression models, adjusting for covariates. Totally 1.6% had asthma, 6.6% allergic rhinitis and 2.2% eczema. Mold odor was associated with asthma (OR = 1.90) and allergic rhinitis (OR = 1.25–1.44). Window pane condensation in winter was associated with asthma (OR = 1.39), allergic rhinitis (OR = 1.26–1.58) and eczema (OR = 1.36–1.77). Presence of mold spots or damp stains was related to asthma (OR = 1.58–2.49), allergic rhinitis (OR = 1.35–1.76) and eczema (OR = 1.47–1.70). Water damage was related to asthma (OR = 1.69–1.82), allergic rhinitis (OR = 1.40–1.45) and eczema (OR = 1.44–1.96). Damp bed clothing was related to asthma (OR = 1.23), allergic rhinitis (OR = 1.23) and eczema (OR = 1.35). A higher dampness score was associated with increased odds ratios for diseases. Those living in older buildings had more asthma (OR = 1.39–1.76) and allergic rhinitis (OR = 1.16–1.21). Those living in suburban or rural areas had less asthma, allergic rhinitis and eczema as compared to those living in urban areas (OR values from 0.24 to 0.66). Stronger health associations with dampness and mold were found in southern China and in newer buildings (constructed after 2005). In conclusion, dampness and mold at home can be risk factors for asthma, allergic rhinitis and eczema among adults in China. Living in older buildings can be risk factors for asthma or allergic rhinitis while living in less urbanized areas can be protective. Highlights: Dampness/mold can be risk factors for adult asthma, allergic rhinitis or eczema. Living in old buildings can be a risk factor for adult asthma and allergic rhinitis. Less urbanized areas have less adult asthma, allergic rhinitis and eczema. High ambient temperature and high precipitation can influence eczema.